(untitled) (Marketing Journal, 2025)
This article examines the issues of enhancing competitiveness in the advertising services market, analyzing foreign best practices and exploring the possibilities of their application in Uzbekistan. The study highlights global trends such as digital transf ormation, innovative marketing strategies, and brand management. The current state of Uzbekistanʼs advertising market is analyzed, along with existing challenges, and practical recommendations are proposed to improve the industryʼs competitiveness based on international experience.